Humboldtia Vahl (Fabaceae): A review on ethnobotany, phytochemistry and pharmacology - Saranya Surendran; A. Chandra Prabha; Raju Ramasubbu; M.V. Krishnaraj (Elsevier, 2021)
Relevance: Humboldtia, a horticulturally potential, ecologically and medicinally valuable genus of subfamily Detarioideae has been reported with 7 species. The information on Ethnobotany, Phytochemistry and Pharmacology has been published with limited articles in reputed journals. Objectives: The main objective was to provide a cumulative information on taxonomy, ethnobotany, phytocompounds and various pharmacological efficiencies of all the species of Humboldtia reported in the world. However, these research works have been limited to only few species and remaining species have not been evaluated phytochemically and pharmacologically. This review provides a decisive interest to work further on the genus Humboldtia. Materials and methods: The systematic search on various aspects of Humboldtia has considered all the articles published in the world between 1830 and 2021 by various scientific data bases. All articles reporting the taxonomy, phytochemistry and pharmacological use of Humboldtia were retained for further investigation. Results: The scientific search by various standard databases provided about 800 articles published between 1830 and 2021 were included. The taxonomy of Humboldtia was still under confusion and about 7 species were published mainly based on morphological features. In general, species of Humboldtia were popularly known as economically important, medicinally valuable and used to cure various diseases and disorders, diabetes, biliousness, leprosy, ulcers, epilepsy, impure blood, demulcent, anthelmintic, stomachic, astringent, menstrual disorders, wounds and urinary troubles. The species of Humboldtia have also reported with various phytochemicals, glycosides, flavonoids, steroids, tannins, phenols, terpenes, tannins, alkaloids, steroids, cardiac glycosides, terpenoids, saponins, phenols, including selective phytocompounds like 2,4-di-tert-butyl phenol, erythrodiol-3-acetate, (2R,3R)-3,5,7,3',5'-pentahydroxyflavone and 3cr-methoxyfriedelan. Various pharmacological experiments were conducted to prove the efficiency of antioxidant, anticarcinogenic, antitubercular, anti-inflammatory, membrane stabilizing and neuropharmacology of different species of Humboldtia. Conclusion: Of the seven species reported, the studies on phytochemistry and pharmacology were restricted to few species H. brunonis, H. vahliana and H. unijuga. Further, studies have to be attempted to know the phytochemistry and pharmacology of the H.bourdillonii, H. decurrens, H.laurifolia, H. sanjappae and H. trijuga. This review will assist the researchers in promoting all branches of botanical researches in Humboldtia and other allied genera.